2018
DOI: 10.1016/j.yrtph.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress responses in human bronchial epithelial cells exposed to cigarette smoke and vapor from tobacco- and nicotine-containing products

Abstract: The use of novel tobacco- and nicotine-containing vapor products that do not combust tobacco leaves is on the rise worldwide. The emissions of these products typically contain lower numbers and levels of potentially harmful chemicals compared with conventional cigarette smoke. These vapor products may therefore elicit fewer adverse biological effects. We compared the effects of emissions from different types of such products, i.e., our proprietary novel tobacco vapor product (NTV), a commercially available hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 40 publications
4
42
0
1
Order By: Relevance
“…Therefore, it is imperative to report the results of this study, tackling the effects of each component of ECIG-generated aerosol trapped in BHI individually. To perform these experiments, we followed an alternative version of already established smoke delivery methods into media [51,52], and compared this to the effects E-liquid components pipetted directly into this broth. This paper also describes the overall biomass of biofilms after exposure to either E-liquid or aerosol trapped in the growth medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is imperative to report the results of this study, tackling the effects of each component of ECIG-generated aerosol trapped in BHI individually. To perform these experiments, we followed an alternative version of already established smoke delivery methods into media [51,52], and compared this to the effects E-liquid components pipetted directly into this broth. This paper also describes the overall biomass of biofilms after exposure to either E-liquid or aerosol trapped in the growth medium.…”
Section: Discussionmentioning
confidence: 99%
“…Air, flavorless ECIG aerosol either with or without nicotine, and smoke were delivered into BHI following a modified version of previously established methodology [51,52] using two Cole-Parmer Master Flex L/S peristaltic pumps (Vernon Hills, IL, USA). One pump setup was used exclusively for smoke.…”
Section: Aerosol and Smoke Trappingmentioning
confidence: 99%
“…The study used four different types of nicotine products, tobacco vapor products, heat-not-burn tobacco products, e-cigarettes, and a combustible cigarette to compare the effects of each product. The result from the study showed possible cell death and reduced function of lung health from the e-cigarette vapor inhalation (Munakata et al, 2018). Another study conducted by Queimado et al (2018), further underscores the dangers associated with the utilization of e-cigarette products.…”
Section: Lung Diseasementioning
confidence: 74%
“…Findings from these two studies are critical because, they show that using e-cigarette products can cause lung cell death, or reduced lung function. It also makes a clear case for why e-cigarettes should not be used as an alternative to tobacco products by adolescents, as the aerosol they inhale, have toxic characteristics (Munakata et al, 2018).…”
Section: Lung Diseasementioning
confidence: 99%
“…Moreover, various next-generation products (NGPs), including e-cigarettes and heat-not-burn tobacco products, have been recently introduced in global markets [3,4]. These NGPs can potentially reduce the harms associated with tobacco use because of their reduced yields of toxicants, which is attributable to the generation of aerosols without combusting tobacco leaves [5,6], but the effects of long-term use of these NGPs on human health remain controversial [7,8] despite previous non-clinical [9][10][11][12] and clinical studies [13][14][15]. Epidemiological analysis could be one of the solutions to estimate the realistic risk of the use of such products, but several years would be needed to reach a conclusion.…”
Section: Introductionmentioning
confidence: 99%